A REVIEW OF PARPATI KALPANA W.S.R. TO RASA PARPATI - Rakheja, *Shefali; Bajaj, Nisha; K Thakur, Sudarshan (International Journal of Ayurveda and Pharma Research, 2018)
Parpati Kalpana is one of the four major pharmaceutical preparations having Parad used in Rasa Shastra. It is one of the 25 Rasa Bandhas which helps to remove the Chanchalatva and Durgrahatva of Parad because by having these two properties, Parad cannot be used internally. Parad and Gandhak are the essential constituents to make Parpati as the Bandha word derived to bind the Parad particle with Gandhak. Parpati is a unique mercurial preparation involving different processes like Murchana, Sagandha/ Nirgandha (presence and absence of sulphur), Sagni (process with heat) Pota Bandha of Parad. The difference of heat provided also differ its therapeutic properties. A detailed literature review regarding Rasa Parpati is collected here. This paper aims the general concept of Parpati with method of preparation of Rasa Parpati and its detailed study. This paper also aiming at new therapeutic values of different Parpati as mentioned in different references. Parpati is mainly used to treat Grahani because of its unique property to dissociate at the intestinal level but during the course of time different Acharyas came with different Parpati having differences in ingredients but having same method of preparation. Thus all Parpati generally have same method of preparation but the differences in ingredients make Parpati having wide range of therapeutics. These wide ranges of Parpati with their therapeutic values are described in this paper.